ASPEK HUKUM PENGGUNAAN KEKAYAAN DALAM PEMENANGAN PEMILIHAN KUWU DI INDRAMAYU TAHUN 2021 - Rasji Rasji; Benny Djaja; Agung Valerama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
In 2021 the Indramayu Regency Government will hold simultaneous kuwu elections in 171 villages. The community welcomed the village democracy party. Kuwu candidates competed quite fiercely in an effort to win their nomination. Kuwu candidates used various methods, including using their wealth in order to win in the kuwu election. What are the legal aspects of the use of assets in winning the Kuwu election in Indramayu in 2021? This problem is interesting to study, with the aim of knowing the legal aspects related to the use of the assets of prospective kuwu in the election of kuwu in Indramayu Regency in 2021. These problems were investigated using normative legal research methods supported by empirical legal research methods. The data collection technique uses a literature study technique on legislation and legal doctrine, which is supported by interview techniques with informants who have competence with the implementation of kuwu elections. The results of the study describe the use of the assets of prospective kuwu in an effort to win the election of kuwu in Indramayu Regency in 2021 containing aspects of state administrative law, aspects of private law, and does not contain aspects of criminal law.